Search for long-lived particles decaying to leptons with large impact parameter in proton–proton collisions at √s = 13 TeV - Tumasyan, Armen; Adam, Wolfgang; Andrejkovic, Janik Walter; Borshch, Vladislav; Ivanchenko, Vladimir; Tcherniaev, Evgueni (The European physical journal C)
A search for new long-lived particles decaying to leptons using proton-proton collision data produced by the CERN LHC at root s = 13 TeV is presented. Events are selected with two leptons (an electron and a muon, two electrons, or two muons) that both have transverse impact parameter values between 0.01 and 10 cm and are not required to form a common vertex. Data used for the analysis were collected with the CMS detector in 2016, 2017, and 2018, and correspond to an integrated luminosity of 118 (113) fb(-1) in the ee channel (e mu and mu mu channels). The search is designed to be sensitive to a wide range of models with displaced e mu ee, and mu mu final states. The results constrain several well-motivated models involving new long-lived particles that decay to displaced leptons. For some areas of the available phase space, these are the most stringent constraints to date.